Proposed marketing strategy of presidents university in education industry in indonesia - Kurniadi, Stevanus; Aditya Wibowo, Satya (The Indonesian Journal of Business Administration, 2018)
Abstract – President University as one of the university that exist in Indonesia offer the international curriculum and standard. Established in 2002, President University offer undergraduate program and graduate program to students in Indonesia which result in creating the leaders that can compete in Asean Economic Community. Having many competitors, President University has a problem in increasing the intake number each year. By that, this paper aims to propose new marketing strategy by that the number of intake student will be increased. The objectives that need to be achieved is to increase the profit of the university by that the expenses will be bigger and the development can happen in order to chase the late improvement compare to other university which already exist many years before President University did. Using some analysis and method, the new marketing strategy can be formulated, more over the weaknesses and threads can be identified for President University in order to take the precaution actions. Many aspects need to be changed from the analysis especially in price aspect. Therefore, President University can target the accurate segment and do the marketing activities effectively and efficiently.